THU0619 Prevalence of pneumococcal vaccination in rheumatologic patients with community acquired pneumonia. biobadasar registry. (15th June 2017) - Gόmez, G; Brigante, A; Benitez, A; Cerda, O; Retamozo, S; Gandino, I; Quinteros, A; Exeni, I; Barrios, B; Astesana, P; Andia, C Sanchez; Collado, MV; et al.
Abstract : Background: Biobadasar is a registry that monitors adverse events in patients who use biological treatments in rheumatologic diseases conducted by the Argentine Society of Rheumatology. As in others international registries the community acquired pneumonia (CAP) has been detected as one of the most frequent infectological adverse events. Although all immunosuppressed patients should be vaccinated against streptococcus pneumoniae, there is a proportion of patients who are not. Objectives: Evaluate the prevalence of pneumococcal vaccination in patients with CAP within the Biobadasar database. Assess factors associated with Severe CAP in these patients. Methods: A cross-sectional, multicentric study was made in BIOBADASAR database from 2010 to2016. In patients who reported CAP data of demographics, comorbidities and state of pneumococcal immunization was collected. Microbiological data, treatment and outcome of the event were considered. The severity of CAP was assessed according to the opinion of the attending physician, hospitalization, risk of life and/or death. Values are expressed as mean ± standard deviation, median (ranges) and frequencies (percentages), as appropriate. We performed bivariate and multivariate logistic regression analysis to identify variables associated with the event. Results: Of the 4029 patients enrolled in the registry, the cumulative incidence of CAP was 4.2% (n 170), 72.4% (n 123) were women. The mean age was 57 (SD +/- 14.5). Biological treatment was found in 81.8% (n 139). Patient s that have received the pneumococcal vaccine were 40.6% (n=69). Severe CAP was detected in 7.1%. Streptococco Pneumoniae was the main pathogen isolated in 13% of the cases. Overall mortality was 4.1%. In the univariate analysis for severe CAP we found statistical significance for Smoking OR 3.88, CI95 1.063–14.22, p= 0.029 and chronic kidney disease (CKD) OR 31, CI95 2.6–376, p= 0.007. When performing a multiple logistic regression model, only renal failure OR 7.39 CI95 0.003–0.38 p= 0.007 was a predictor of severe CAP. Not significative association with immunosuppressive treatment (p: 0.09), age (p: 0.464), or vaccination (p: 0.937) Conclusions: The annual incidence of CAP in Argentina varies between 0.5 -1.1% while in our cohort it was four times higher. The prevalence of pneumococcal vaccination was less than 50%, showing that, although the literature and guidelines establish the need for vaccination, this is not so in the real world. In the multivariate analysis, only CKD was related to severe CAP. Although in the univariate analysis the CKD and the smoking habit represented factors associated with severity. We must emphasize the medical education in following the international vaccination guidelines. Disclosure of Interest: None declared